PENERAPAN STRATEGI INTERVENSI DALAM PEMBELAJARAN IPA UNTUK MEMACU PERKEMBANGAN KEMAMPUAN BERPIKIR SISWA PADA USIA PERALIHAN DI SEKOLAH DASAR - , ERMAN (Pendidikan Dasar, 2009)
Abstract: This study aims to induce students’thinking ability by an intervention strategy through sains learning. As long as four months, fifty four students of SDN Puhsarang I and Puhsarang II Kediri inducing their cognitive thinking through three matter, water, stone and earth respectively. Data is collected by using SCDT (science cognitive development test). The target is achieved after conducting two learning cycles refer to the action research method. The result shows that after the first cycle, there are only 35.19% students can operate concrete reasoning completely (C2) where by 64.18% students are still on the basic category of concrete reasoning. But, after the second cycle or four month intervention, the number of students who could operate concrete reasoning completely become 74.10% where by there are only 25.90% students are still on the basic level. These facts indicate that intervention period or four months is not enough to stimulate students’abstract reasoning in the transition periode. Learning activity must be paying more attention on students’reasoning and make an intervention systematicaly.